(m-2)(m²+2m+4)-2m(m²-3),其中m=2
2个回答
答:
(m-2)(m²+2m+4)-2m(m²-3)
=m³+2m²+4m-2m²-4m-8-2m³+6m
=-m³+6m-8
=-2³+12-8
=-4
相关问题
化简求值:[(3m/(m+2)-m/(m-2)]/[(2m)/m^2-4)],其中m=2/3
化简求值:(-m^4/m^2)^2+(-2m)^3*m^2+(-m^2)^4/m^4,其中m=-1
(m+2/m^2-2m)-(m-1)/(m^2-4m+4)除以m-1/m,其中m=4
化简并求值(m-2)(m²+2m+4)-2m(m²-3),其中m=2
先化简,再求值:4m3-(3m2+5m-2)+2(3m+[3/2]m2-2m3)-1,其中m=2011.
先化简,再求值:4m3-(3m2+5m-2)+2(3m+3 2 m2-2m3)-1,其中m= 2 009
(1)M^2+M-3M^2-5M+2M^2+4=?(M=-3/4)
(m²-2m+1/m²-1+m²-m/m)÷(1+m/2,其中m=-3)
设复数z=(m2-2m-3)+(m2+3m+2)i,其中m∈R.
求2/5m-(3/2m-1)+3(4-m)的值,其中m=-3